WHY AFTERIMAGES ARE METAPHYSICALLY MYSTERIOUS. Issue 49 (23rd May 2018) - Frances, Bryan
Abstract : Given how important colour is to us, it's not surprising that we have learned a great deal about colour over the centuries. However, what is much less well known – almost completely unknown outside philosophy – is the fact that colour remains a mystery : there are some simple facts about colour that lead to paradoxes that no one has been able to solve for centuries .